2006
DOI: 10.1063/1.2358987
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond coherent anti-Stokes Raman-scattering polarization beat spectroscopy of I2–Xe complex in solid krypton

Abstract: Time-resolved coherent anti-Stokes Raman-scattering (CARS) measurements are carried out to study the interaction between xenon atom and iodine molecule in a solid krypton matrix. Interference between the CARS polarizations of the "free" and complexed iodine molecules is observed, while the quantum beats of the complex are not detected due to low concentration. Vibrational analysis based on the polarization beats yields accurate molecular constants for the I2-Xe complex. The harmonic frequency of the I2-Xe comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 63 publications
3
20
0
Order By: Relevance
“…When the matrix sample was doped with Xe = 0.1%, in addition to signal from I 2 we could observe definite signal from isolated 1:1 I 2 -Xe complex. 22,28 The fs-CARS characterization of the matrix with Xe = 0.1% essentially reproduced the our earlier results for high vibrational wavepacket 22 showing that the matrix with Xe = 0.1% already contains significant amount of I 2 -Xe complex (see supplementary material S2 for details of the fs-CARS measurements 29 ).…”
Section: Fs-cars and Pump-probesupporting
confidence: 73%
See 2 more Smart Citations
“…When the matrix sample was doped with Xe = 0.1%, in addition to signal from I 2 we could observe definite signal from isolated 1:1 I 2 -Xe complex. 22,28 The fs-CARS characterization of the matrix with Xe = 0.1% essentially reproduced the our earlier results for high vibrational wavepacket 22 showing that the matrix with Xe = 0.1% already contains significant amount of I 2 -Xe complex (see supplementary material S2 for details of the fs-CARS measurements 29 ).…”
Section: Fs-cars and Pump-probesupporting
confidence: 73%
“…Kiviniemi et al have previously characterized in great detail the effect of Xe on the I 2 ground state vibrational frequency in Kr matrices using the fs-CARS technique. 28 In this earlier publication by our group it was estimated from the band amplitudes of I 2 and I 2 -Xe complex that a ratio as high as ∼1/3 of the I 2 molecules are in the 1:1 complex form, when Xe to Kr ratio is 0.1% and I 2 /Kr = 1/2600. Our CARS results, where we have prepared our matrices with identical gas ratios and matrix preparation parameters (temperature, flow rate) are in a good qualitative agreement with the earlier results, implying that in our case at least significant part of the iodine molecules are in the 1:1 complex form (see supplementary material S2 for details 29 ).…”
Section: A Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, single-shot measurements can be readily achieved with a substantial increase in the signal-to-background ratio over that possible with ns-CARS [7]. However, the increased laser bandwidth can simultaneously excite other species that have nearby Raman transitions; hence, the observed CARS signal may consist of interference beatings between various Raman transitions, which complicates the interpretation of the measured CARS signal [13][14][15][16][17]. In this case, the temporally resolved fs-CARS signal recorded will consist of a modulation pattern that results from the beating between the two or more Raman polarizations involved.…”
Section: Introductionmentioning
confidence: 99%
“…Knopp et al 10 showed that femtosecond tr CARS spectroscopy is a powerful tool for the investigation of collision-induced linewidths and the validation of rotational energy transfer models. Kiviniemi et al 11 studied the polarization beat spectroscopy of I 2 -Xe complex in solid krypton using the tr CARS technique. Tran et al 12 carried out measurements and modeling of femtosecond tr CARS signal in H 2 -N 2 mixtures at low densities.…”
Section: Introductionmentioning
confidence: 99%